Antioxidant bioactivity of sunflower protein hydrolysates in Caco-2 cells and in silico structural properties - Lopes, Daniel S; Almeida, Lilian G V C; Nardo, Agustina E; Añón, María Cristina; Dos Santos, Lucilene D [UNESP]; Rossini, Bruno C [UNESP]; Pinilla, Cristian M B; Pacheco, Maria T B; Galland, Fabiana (Elsevier, 2025)
Sunflower protein hydrolysate (SPH), with 95 % reduced phenolic content, was studied for its protective effects against oxidative stress in intestinal cells (Caco-2). Produced via alcalase hydrolysis, SPH's molecular weight, amino acid composition, and hydrophobicity were characterized. The antioxidant activity of SPH, tested by ABTS, was maintained in Caco-2 cells under oxidative stress, modulating glutathione and catalase enzymes. LC/MS/MS identified 196 peptides, which were cross-referenced with a bioactive database and found to contain several di- and tripeptides with antioxidant activity. Higher hydrophobicity and molecular weight correlated with predicted antioxidant and anti-inflammatory activity scores, provided by tools that use machine learning methods. The study shows that SPH exhibits antioxidant properties in enterocyte cell models, even with reduced phenolic content, suggesting its potential use in functional foods.